EFFECT OF DIFFERENT HERBAL DRUGS ON AVERAGE LITTER SIZE OF TAMWORTH> - KUMAR, SUDHIR; SINHA, A K; KUMAR, SUDERSHAN; J NAIDU, SHARAD (The Indian Journal of Animal Reproduction, 2023)
This experiment was undertaken to study the effect of herbal preparations viz; Femelin, Lecorin plus and Asoka cordial on reproductive trait such as litter size in 55 TamworthxDesi breed sows allocated into 4 groups. The superiority in I itter size in Lecorin Plus treated group (T 2) and Asoka cordial treated group (T 3) were observed during entire preweaning period and also up to weaning day ie.561h day. However, the effect had statistically nonsignificant on litter size.